Headache associated with sexual activity - Jokubaitis , M.; Ryliškienė , K. (Neurologijos seminarai, 2021)
Headache associated with sexual activity (HSA) is a type of primary headache disorder that is precipitated by sexual activity. The reported prevalence of HSA is about 1-1.6%. Nonetheless, it is possible that the incidence of the disease may be much higher due to patient’s unwillingness to express sexual activity-related complaints. HSA is linked to a high rate of other primary headache disorders. Treatment of HSA consists of acute pain management and headache recurrence prevention. This article reviews the epidemiology, pain characteristics, diagnostic criteria, differential diagnosis, and treatment of HAS. The impact of sexual activity on acute attacks of primary headache disorders and the comorbidity of primary headache and sexual dysfunction are also discussed.